Lobsters as Part of Marine Ecosystems – A Review - Phillips, Bruce; Wahle, R.; Ward, T. (John Wiley & Sons, Ltd, 2013)
Lobsters are the focus of valuable fisheries worldwide; they are often regional icons, and mainly because of this are among the most researched animals on earth. As fishery management moves globally from a single-species to an ecosystem-based emphasis, it remains important to understand the role of species functions in marine ecosystems. Despite the wealth of research on lobsters, our understanding of their role in marine ecosystems is patchy. As mid-trophic-level consumers, lobsters function in the transfer of energy and materials from primary producers and primary consumers to apex predators. They are large-bodied and conspicuous, and can comprise a considerable proportion of the collective consumer biomass. Still, the nature and strength of interactions, and the relative importance of top-down and bottom-up effects to their productivity is murky. Australia, the USA, the European Union, Canada and New Zealand are beginning to implement ecosystem-based fishery management. Here, we review two case studies from dramatically contrasting ecosystems: the spiny (rock) lobster Panulirus cygnus in subtropical Western Australia, and the American lobster Homarus americanus in cool temperate eastern North America. Our analysis identifies knowledge gaps and takes a first step in evaluating the consequences of differing ecosystem-based management approaches to these and other lobster fisheries.